2002
DOI: 10.1080/20024091064264
|View full text |Cite
|
Sign up to set email alerts
|

Review and Evaluation of the Potential Impact of Age- and Gender-Specific Pharmacokinetic Differences on Tissue Dosimetry

Abstract: In standard risk assessment methods for carcinogenic or noncarcinogenic chemicals, quantitative methods for evaluating interindividual variability are not explicitly considered. These differences are currently considered by the use of statistical confidence limits or default uncertainty factors. This investigation consisted of multiple tasks aimed at making quantitative predictions of interindividual differences in susceptibility by using physiologically based pharmacokinetic (PBPK) models. Initially, a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 42 publications
1
118
2
2
Order By: Relevance
“…This value in the adult lung varies from 200 to 600 million. At birth, the alveolar surface area is approximately 3 m 2 ; while in adults, the alveolar surface area is 75 m 2 (Clewell et al, 2002). Considering such values of alveolar surface area, Fig.…”
Section: Regional Particle Deposition In the Respiratory Systemmentioning
confidence: 99%
“…This value in the adult lung varies from 200 to 600 million. At birth, the alveolar surface area is approximately 3 m 2 ; while in adults, the alveolar surface area is 75 m 2 (Clewell et al, 2002). Considering such values of alveolar surface area, Fig.…”
Section: Regional Particle Deposition In the Respiratory Systemmentioning
confidence: 99%
“…Volatile compounds like the THMs are eliminated from the body rapidly after the exposure ceases and hence the biomarker concentrations are highly sensitive to recent exposures. Recent exposure is of less concern for highly persistent compounds like dioxin, but the biomarker concentrations in this case could be affected by physiological changes such as growth or altered body fat content (Clewell et al, 2004). These considerations need to be explicitly characterized and quantified before it will be possible to interpret biomonitoring data for these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsberg et al (2005) indicated that the particle dose in the pulmonary region is also likely to be two to four times higher in three-month-old children than in adults, particularly for submicrometre-size particles. The skin surface area relative to body weight is greater in children than in adults, such that the potential dose received following dermal exposure is likely to be about three times greater in infants than in adults (Clewell et al, 2002). The permeability of the epidermal barrier is poorly developed in the preterm infant, resulting in greater percutaneous absorption of chemical agents.…”
Section: Absorption Distribution Metabolism and Eliminationmentioning
confidence: 99%
“…bromosulfthalein, bilirubin), for example, are longer in newborns than in adults. Renal clearance has been shown to be lower in neonates than in older children and adults, for all chemical classes: lipophilic, hydrophilic, and organic ions (Clewell et al, 2002). Glomerular filtration rate at normal-term birth is about one third of the adult value when expressed on the basis of body surface area and matures in about six months.…”
Section: Absorption Distribution Metabolism and Eliminationmentioning
confidence: 99%
See 1 more Smart Citation